Some effects of anaerobic ageing, stress softening and recovery on the modulus and damping of certain NR vulcanisates for anti-seismic bearings - Pond T J (Journal of Rubber Research, 1999)
Data are shown which quantifies and helps to predict some effects of anaerobic ageing and repeated shear deformations on the modulus and damping properties of selected high damping NR vulcanisates. For such vulcanisates the results show that at a given ageing temperature the increase in modulus associated with anaerobic ageing can be reasonably accurately predicted when plotted as a function of the square root of the ageing time. Measurements showing the influence of different tests strains and the number of cyclic deformations at a constant stain on the modulus and damping properties of these vulcanisates are also given. Some cumulative effects of anaerobic ageing, stress sofening and recovery on the modulus and damping properties during certain applied strain histories relevant to anti-seismic bearings are also shown. Such results indicate that stress softening can have the dominant effect on the modulus of a vulcanisate at small strains whereas at larger strains anaerobic ageing can be the dominant factor.
Keywords: Anaerobic ageing; Anti-seismic bearing; Damping; NR vulcanisates; Stress softening